Chapter Introduction 'Infrastructural Compendia' and the Licensing of Empiricism in Mesopotamian Technical Literature - Johnson, J. Cale (De Gruyter, 2015)
In the Wake of the Compendia examines the composition of technical literature in the ancient Semitic-speaking world. Compendia on astrology, magic, medicine, lexicography, and alchemy were composed in several languages and relate to earlier Mesopotamian models. This volume offers new perspectives on the early history of these compendia and their subsequent transmission into later post-cuneiform compilations, curricula, and scholarly writings.